A companion to British art : 1600 to the present - Arnold, Dana; Peters Corbett, David, 1956- (Hoboken : Wiley-Blackwell, 2013)
Provides a diverse collection of essays addressing key issues for European art produced between 1300 and 1700, a period that might be termed the beginning of modern history.
pt. 1. Editors' introduction -- pt. 2. General -- pt. 3. Institutions -- pt. 4. Nationhood -- pt. 5. Landscape -- pt. 6. Men and women.
Includes bibliographical references and index.
Print version record.
Keywords: Art, British; ART -- European; Art, British; Electronic books; Electronic books